Analysis of the Higher Education Backgrounds of Nobel Prize Laureates in Physiology or Medicine from 2000 to 2024 - Jianlin HOU; Yujie HUANG (Yixue yu zhexue)
Between 2000 and 2024, there were a total of 60 individuals received the Nobel Prize in Physiology or Medicine, of which 59 came from developed countries such as the United States, the United Kingdom, Japan, and France, and only 1 came from China. The higher education backgrounds of the laureates reflect a combination of localization and internationalization, with most having studied in top universities around the world. The vast majority of the laureates' undergraduate majors are non-medical majors. Some laureates have interdisciplinary dual doctoral degrees or cross-border learning experiences. In China, special attention should be paid to the important role of top universities and high-quality educational environments in cultivating top-notch innovative talents in medicine. Furthermore, interdisciplinary education, the cultivation of international perspectives, innovative thinking, and research interests, also need to be emphasized.